If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 18 = 6x + 8 Reorder the terms: 18 + 4x = 6x + 8 Reorder the terms: 18 + 4x = 8 + 6x Solving 18 + 4x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 18 + 4x + -6x = 8 + 6x + -6x Combine like terms: 4x + -6x = -2x 18 + -2x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 18 + -2x = 8 + 0 18 + -2x = 8 Add '-18' to each side of the equation. 18 + -18 + -2x = 8 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 8 + -18 -2x = 8 + -18 Combine like terms: 8 + -18 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 7(2x+7)=4+50 | | (5v+3)(9-v)=0 | | 6(m+3)+8(4m+1)=37(m+1)-5 | | 7r-5(3r-7)=51 | | u/5=17/8 | | .03(6x+3)=2x-5 | | 8(x+9)+3a(x+9)= | | 2x^4-15x^2+27=0 | | -9(t+4)+8(3t+1)=(t-4)+7 | | 4(x+4)=4+9x | | 3x-6=2+21 | | 6x+12(3x-4)=19+7x | | (3-x)[(3-x)(-x)-(4)]-2[2(3-x)-8]+4[4+4x]=0 | | -9(t+4)+8(3t+1)= | | x+9+a(x+9)= | | 88-2x=6-9x | | 1/7(x+5)-1/2(x+4)=-2 | | -35=-5y | | 10x+15=3(3x+2) | | 20=m-19 | | 18-30= | | -6.75=u/7+2 | | -8u+15.9=3.1 | | 5k+8=3k-1 | | (-x^2)+x+23=0 | | -14.9=-2.1+y/2 | | 7x/1x | | 8p-4p=24 | | (x^2)+x+23=0 | | 4d-12=2d | | 2x(2x+1)(x-5)=0 | | -(-2-3u+5)= |